'To test or not to test', the arguments for and against thrombophilia testing in obstetrics. (June 2017) - Ormesher, Laura; Simcox, Louise E; Tower, Clare; Greer, Ian A
Clinicians increasingly investigate women for thrombophilias due to their associations with venous thromboembolism and placenta-mediated pregnancy complication. These associations, however, are modest and based largely on retrospective data from studies with heterogeneous classifications and populations, leading to discordance between evidence and guidelines. Current evidence suggests a contributory rather than causative role for thrombophilia in placenta-mediated pregnancy complication and venous thromboembolism. With little evidence of benefit from antithrombotic therapy in placenta-mediated pregnancy complication, thrombophilia screening remains controversial. Given the low absolute risk of placenta-mediated pregnancy complication and gestational venous thromboembolism with heritable thrombophilia, universal screening is inappropriate. Selective screening for antiphospholipid syndrome is supported by robust evidence of benefit. Conversely, selective screening for heritable thrombophilia has not been shown to effectively manage placenta-mediated pregnancy complication. Therefore, at present heritable thrombophilia screening is not warranted for placenta-mediated pregnancy complication. Until we have better evidence from better stratified patient groups, caution should remain if we wish to practice evidence-based medicine.